FORMATION OF MARKETING-ORIENTED APPROACH TO PROVIDING INNOVATIVE PRODUCTS OF INDUSTRIAL ENTERPRISE - Nikolaenko , Yu.V.; Lavrov , R.V. (The actual problems of regional economy development, 2019)
In the article the questions of marketing support of innovations of domestic industrial enterprises in the conditions of international economic relations are considered. The features of marketing of innovations are justified; the tasks of marketing of innovations at different stages of itsimplementation are defined; sequencing of marketing of innovations is suggested; the stages of the process of perception of innovations by different groups of consumers are investigated. The commercial success of innovations on the market is impossible without their active marketing support. Analysis of domestic and foreign scholars on the problems of marketing of innovations has revealed that in spite of they have developed theoretical and methodological approaches to the formation of a complex of marketing innovation, there are no methodological developments in the organization and application of marketing innovation in the enterprise. The sequence of implementation of marketing innovations in the context of international economic relations will allow industrial enterprises to form an effective marketing strategy, even at the stage of their creation is proposed. Marketing innovation needs to take place at all stages of the innovation process that will ensure the competitiveness of innovative products in the international market. Studies have shown that the main criteria that determine the demand for innovation of enterprises in the conditions of international economic relations are: the ability to meet the needs of consumers; distinct competitive advantage; ease of use; the ability to test features that are stated in the product. Innovative products will be in demand in the market, if it is to have at least one unique characteristic that will be important for consumers.